2018
DOI: 10.26842/binhm.7.2018.15.1.0041
|View full text |Cite
|
Sign up to set email alerts
|

List of Insects Associated With Macrofungi in Tikrit City, Salahadin Governorate, Iraq

Abstract: In this survey, there are 14 species belonging to 14 genera, nine families and two orders, collected on Macrofungi from Tikrit city, Salahadin Governorate, North Central of Iraq. The members of Coleoptera were more abundant than flies on Macrofungi. The family of Ciidae and Leiodidae (Order, Coleoptera), Mycetophilidae (Order, Diptera), and 6 species are recorded for the first time for insect fauna of Iraq.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Cis multidentatus (Pic 1917) sensu Lohse & Reibnitz 1991: 104 [42] {reported from Italy and Germany}; Jelínek 2008: 57 [32] {records from Italy and Germany}; Lopes-Andrade 2008: 42 [7] {reported from Malta}; Shugran et al 2018: 42 [43] {reported from Iraq}.…”
Section: Resultsmentioning
confidence: 99%
“…Cis multidentatus (Pic 1917) sensu Lohse & Reibnitz 1991: 104 [42] {reported from Italy and Germany}; Jelínek 2008: 57 [32] {records from Italy and Germany}; Lopes-Andrade 2008: 42 [7] {reported from Malta}; Shugran et al 2018: 42 [43] {reported from Iraq}.…”
Section: Resultsmentioning
confidence: 99%
“…(Amini et al, 2014(Amini et al, , 2015. Distribution in Palearctic: China (Lawrence, 1991), France (Rose, 2009), Germany (Lohse & Reibnitz, 1991), Hungary (Reibnitz & Kunz, 2011), Malta (Lopes-Andrade, 2008), Spain (Diéguez Fernández, 2013), Iraq (Shugran et al, 2018). Report from Iran about Cis multidentatus (Pic, 1917) (Amini et al, 2014) Widespread Palearctic species.…”
Section: List Of Speciesmentioning
confidence: 99%
“…In the last few years, many researchers have sought to conduct many studies that include the preparing of surveys and checklists of insect species belonging to different orders. These investigations have contributed to updating databases and treating synonyms in order to avoid mistakes in taxonomic issues and contribute to knowing the insect diversity in Iraq, for example: Shugran et al (2018); Augul (2018Augul ( , 2019; Augul and Al-Saffar (2019); Hassan et al (2020); Al- Augul (2015, 2021) and Al-Saffar et al(2021).…”
Section: Introductionmentioning
confidence: 99%